Set Up William Forsythe - Mackrell, Judith (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Such was the outrage directed at Frankfurt that the discomfited council ended up helping to fund Forsythe in a brand new venture. PALABRAS CLAVE: William Forsythe, Ballet Frankfurt, The Forsythe Company.